2000
DOI: 10.1091/mbc.11.11.3963
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiaePTS1 Receptor Pex5p Interacts with the SH3 Domain of the Peroxisomal Membrane Protein Pex13p in an Unconventional, Non-PXXP–related Manner

Abstract: A number of peroxisome-associated proteins have been described that are involved in the import of proteins into peroxisomes, among which is the receptor for peroxisomal targeting signal 1 (PTS1) proteins Pex5p, the integral membrane protein Pex13p, which contains an Src homology 3 (SH3) domain, and the peripheral membrane protein Pex14p. In the yeast Saccharomyces cerevisiae, both Pex5p and Pex14p are able to bind Pex13p via its SH3 domain. Pex14p contains the classical SH3 binding motif PXXP, whereas this seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 61 publications
6
118
0
Order By: Relevance
“…Prominent examples are two typical WXXX(F/Y) motifs of S. cerevisiae Pex5 (18,21) or one of the three WXXX(F/Y) motifs of Trypanosoma brucei Pex5 (22). These sequences may mediate the interaction with other peroxins, as shown for human and yeast Pex5 motifs, which both can interact with the Src homology 3 domain of Pex13 (8,13,24,25).…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 98%
See 1 more Smart Citation
“…Prominent examples are two typical WXXX(F/Y) motifs of S. cerevisiae Pex5 (18,21) or one of the three WXXX(F/Y) motifs of Trypanosoma brucei Pex5 (22). These sequences may mediate the interaction with other peroxins, as shown for human and yeast Pex5 motifs, which both can interact with the Src homology 3 domain of Pex13 (8,13,24,25).…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 98%
“…A peroxisomal membrane complex consisting of Pex13 and Pex14 (and Pex17 in yeast) provides the primary docking site for the cargo-loaded receptors (7,8). Pex14 fulfills additional important functions in cargo translocation across the peroxisomal membrane.…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 99%
“…In mammals, GST (glutathione transferase)-PEX13 pull-down assays have shown that the N-terminal 100 amino acids provide a binding domain for PEX5 (Otera et al, 2002), whereas in yeast, pull-down and two-hybrid assays have shown that the C-terminal SH3 (Src homology 3) domain provides a binding site for Pex5p (Bottger et al, 2000;Urquhart et al, 2000). A. thaliana PEX7 also bind the N-terminus of PEX13 in a yeast two-hybrid assay (Mano et al, 2006).…”
Section: Docking Complexmentioning
confidence: 99%
“…In S. cerevisiae, the pentapeptide motifs have been demonstrated to be involved in the interaction of Pex5p with Pex13p (5). However, mutation of the motifs did not affect the binding of Pex5p with Pex14p, implying that the WXXXF/Y motifs are not involved in such an interaction (5). Whether or not the WXXXF/Y motifs are involved in the interaction of mammalian Pex5p with Pex13p has not been reported, but seven pentapeptide motifs in human Pex5pL have been shown to bind Pex14p in vitro with different affinities (35).…”
mentioning
confidence: 96%
“…Pex5p is composed of two distinct parts, a highly conserved C-terminal half comprising seven tetratricopeptide repeat (TPR) motifs and an N-terminal half in which only a few amino acids are strictly conserved, typically in the multiple pentapeptide WXXXF/Y repeats (5,36). While the TPR region was shown to mediate the binding to PTS1-containing proteins (18), specific functions were not fully assigned to the N-terminal half.…”
mentioning
confidence: 99%